Analysis of the Relationship Between Effectiveness and Employee Job Success in the Processing of Border Crossing Permits to Improve Service Quality to the Public at the Class II Immigration Office, Immigration Checkpoint (TPI) Atambua, Belu Regency - Selviana Veronika Moruk (Yayasan Nurul Musthafa, 2025)
The purpose of this study is to examine the relationship between effectiveness and the success of immigration officers in processing border crossing permits to improve the quality of public services; to identify the supporting and inhibiting factors affecting the effectiveness and success of immigration officers in processing these permits; and to provide solutions for the Head of the Immigration Office to enhance employee effectiveness and success in this regard. The research employed a quantitative descriptive approach. The results show a strong relationship between the effectiveness and job success of employees in processing border crossing permits, aimed at improving public service quality at the Class II Immigration Office, TPI Atambua, Belu Regency, as evidenced by a Pearson correlation coefficient of 0.9604. Supporting factors, which scored above 3.51, include acting with honesty, requesting employee reports, planning payment tariffs, and applicants’ satisfaction with the quality of the permit issuance process. Inhibiting factors, which scored between 0.50 and 2.50, include lack of experience in processing permits, unclear job responsibilities, unfriendliness toward applicants, lack of diligence, absence of permit issuance targets, weak staff assignment planning, issues in inputting applicant data into the information system, and generally poor service quality. [Kegunaan dari penelitian ini adalah untuk mengetahui hubungan efektivitas dengan keberhasilan kerja pegawai imigrasi dalam pengurusan surat lintas batas demi meningkatkan mutu pelayanan kepada masyarakat, untuk mengidentifikasikan faktor -faktor yang mendukung dan menghambat efektivitas dan keberhasilan kerja pegawai imigrasi dalam penegurusan surat izin lintas batas demi meningkatkan mutu pelayanan kepada masyarakat, untuk memberikan jalan keluar kepada Kepala Kantor Imigrasi dalam meningkatkan efektivitas dengan keberhasilan kerja pegawai imigrasi dalam pengurusan surat izin lintas batas demi meningkatkan mutu pelayanan kepada masyarakat di Kantor Imigrasi Kelas II TPI Atambua Kabupaten Belu Adapun pendekatan penelitian yang digunakan adalah deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa terdapat hubungan yang kuat antara Analisis Hubungan efektivitas dengan keberhasilan kerja pegawai dalam pengurusan surat izin lintas batas demi meningkatan mutu pelayanan kepada masyarakat di Kantor Imigrasi Kelas II TPI Atambua Kabupaten Belu yang dibuktikan dengan koefesien korelasi r product moment yang diperoleh sebesar 0,9604. Faktor – faktor pendukung adalah faktor- faktor yang mendapat skor 3,51 ke atas yaitu faktor jujur bertindak, meminta laporan pegawai, rencana tarif pembayaran, kepuasan pemohon pembuatan surat izin lintas batas dengan keadaan baik. Faktor yang menghambat disiplin dengan prestasi kerja adalah faktor yang mendapat skor 0,50- 2,50, yakni faktor berpengalaman mengurus surat izin lintas batas, mengetahui tugas, ramah kepada pemohon pembuatan surat izin lintas batas, rajin bertugas, rencana target penerbitan surat izin lintas batas, rencana penugasan pegawai, penaskahan pemohon pembuatan surat izin lintas batas dalam sistem informasi, kualitas pelayanan dengan keadaan kurang baik.]